Population Pharmacokinetic Analyses of Ertugliflozin in Select Ethnic Populations. Issue 11 (2nd July 2021) - Fediuk, Daryl J.; Sahasrabudhe, Vaishali; Dawra, Vikas Kumar; Zhou, Susan; Sweeney, Kevin
Abstract: Ertugliflozin, a sodium‐glucose cotransporter 2 inhibitor, is approved for treatment of type 2 diabetes. Two population pharmacokinetic (PK) analyses were conducted, using data from up to 17 phase 1 to 3 studies, to characterize ertugliflozin PK parameters in select ethnic subgroups: (1) East/Southeast (E/SE) Asian vs non‐E/SE Asian subjects; (2) Asian subjects from mainland China vs Asian subjects from the rest of the world and non‐Asian subjects. A 2‐compartment model with first‐order absorption, lag time, and first‐order elimination was fitted to the observed data. For the E/SE Asian vs non‐E/SE Asian analysis (13 692 PK observations from 2276 subjects), E/SE Asian subjects exhibited a 17% increase in apparent clearance (CL/F) and 148% increase in apparent central volume of distribution (Vc/F) vs non‐E/SE Asian subjects. However, individual post hoc CL/F values were similar between groups when body weight differences were considered. For the second analysis (16 018 PK observations from 2620 subjects), compared with non‐Asian subjects, CL/F was similar while Vc/F increased by 44% in Asian subjects from mainland China and both CL/F and Vc/F increased in Asian subjects from the rest of the world (8% and 115%, respectively) vs non‐Asian subjects. Increases in Vc/F would decrease the ertugliflozin maximum concentration but would not impact area under the concentration‐time curve. Therefore, the differences in CL/F (area under the concentration‐time curve) and Vc/F were not considered clinically relevant or likely to result in meaningful ethnic differences in the PK of ertugliflozin.